2017
DOI: 10.1021/acscatal.6b03166
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Deactivation in Pyridine-Assisted Selective Dehydration of Methyl Lactate on NaY

Abstract: Acrylic acid is a major commodity chemical currently produced almost entirely from petroleum-derived sources. The catalytic dehydration of methyl lactate is a promising renewable route to producing this vital chemical feedstock; however, enhancing the selectivity toward the dehydration pathway and catalyst stability remain challenging. We demonstrate a selectivity for dehydration products of ∼90% over a period of 30 h on NaY by introducing a small amount of pyridine in the reactant feed (pyridine/methyl lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(71 citation statements)
references
References 81 publications
4
67
0
Order By: Relevance
“…Murphy et al. suggested that the formation of acetaldehyde over NaY zeolite is taking place over Brønsted acid sites However, recently Sad et al. reported a study showing that protonic forms of zeolites, viz .…”
Section: Chemical Routes Of Acrylic Acidmentioning
confidence: 99%
See 3 more Smart Citations
“…Murphy et al. suggested that the formation of acetaldehyde over NaY zeolite is taking place over Brønsted acid sites However, recently Sad et al. reported a study showing that protonic forms of zeolites, viz .…”
Section: Chemical Routes Of Acrylic Acidmentioning
confidence: 99%
“…To reveal a possible reaction mechanism of the dehydration of ML on zeolites, Murphy et al. performed an in‐situ FTIR study of ML conversion over NaY (Scheme ) . They suggested that similar to lactic acid, the first step of the dehydration reaction is a dissociative adsorption of ML on zeolite surface with the intermediate formation of a surface sodium lactate species.…”
Section: Conversion Of Alkyl Lactates and Derivatives To Alkyl Acrylatesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the wavenumber of the O−H stretching band of BAS on faujasites is not a reliable descriptor for their acidity . The dissociative adsorption generates a corresponding sodium salt species, which is identified via a unique ν([O−C−O] − ) mode typically located in the range of 1550–1650 cm −1 in FTIR spectroscopy . In a previous study, we demonstrated that molecules with gas‐phase deprotonation enthalpy (GPDE) below ∼1625 kJ/mol generated clear vibrational bands for BAS and corresponding sodium salts when adsorbed on NaY, while molecules with GPDE above this threshold did not.…”
Section: Introductionmentioning
confidence: 99%